Pendampingan Branding Bagi Pelaku Usaha Mikro Makanan Minuman (UMKM) di Kecamatan Grati Kabupaten Blitar - Tri Wahyudi, Setyo; Badriyah, Nurul; Kartika Sari; Nabella, Rihana Sofie; Radeetha (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2026)
In developing MSMEs, the government, community, and educational institutions can provide support, especially in terms of providing branding training. Research shows that branding can increase the competitiveness of MSMEs, and factors such as product quality, price, and promotion influence it. Therefore, this activity aims to provide 'branding' assistance for Micro Food and Beverage Business Actors (MSMEs) in Grati District, Pasuruan Regency. This is done to support the increase in women's empowerment in managing MSMEs in the area by involving Fatayat NU Grati District as a partner. This community service activity began with identifying partner problems (Fatayat NU Grati District) by dividing them into groups accompanied by the FEB UB Community Service team. The community service results revealed that partners' primary issue was a lack of understanding about product branding procedures, which led to less attractive product labeling, limited word-of-mouth marketing, and limited funding.